Static and dynamic performances of sandwich plates with magnetorheological elastomer core: Theoretical and experimental studies. (March 2022) - Li, Hui; Wang, Wenyu; Wang, Qingshan; Han, Qingkai; Liu, Jinguo; Qin, Zhaoye; Xiong, Jian; Wang, Xiangping
This paper investigates the static and dynamic performances of sandwich plates with magnetorheological elastomer (MRE) core, in which the MRE core includes two copper wire layers, two inner metal layers, and one MRE layer. First, based on the complex modulus method, the Jolly theory and the pre-defined magnetic coefficients, the dynamic moduli, and loss factors of MRE are assumed as a function of magnetic induction intensity. Furthermore, a theoretical model of the MRE sandwich plates (MRESPs) is proposed, which considers the internal magnetic field excitation and four types of panel materials, namely fiber-reinforced polymer (FRP), fiber-reinforced polymer with carbon nanotubes (CNT-FRP), metal and fiber-metal hybrid (FMH) panels. After the deformation and energy equations are derived to solve the static bearing stiffness, dynamic stiffness, and damping parameters, some literature results are employed to provide the initial validation of the model developed. Subsequently, four MRESP specimens with the FRP, CNT-FRP, metal, and FMH panels are fabricated and measured to further verify the model as well as to evaluate the mechanical performance. The influence of critical geometric and material parameters related to MRE on static and dynamic properties is also discussed to summarize some practical conclusions for engineering applications.